Improving quality management in community colleges in Kingdom of Saudi Arabia - Aljanobi, Mansour Abdulrhman (2015)
Organizations around the world are seeking to maximize their success and sustainability to survive in today’s rapidly changing world – by improving the quality of their products and services, responding to clients’ needs, and maximizing customer satisfaction. Quality, in turn, needs to be well managed to guarantee good services or products.